SURVIVAL AND GROWTH OF BARU (Dipterix alata Vog.) TREATED WITH SEWAGE SLUDGE, COMPOSTED GARBAGE OR CATTLE MANURE ON MINED SPOILS IN THE BRAZILIAN CERRADO - Cristiane de Queiroz Pinheiro; Lucas de Carvalho Ramos Silva; Rodrigo Studart Corrêa (Revista Sociedade & Natureza, 2005)
Sewage sludge and composted garbage are available in large quantities to be employed assources of organic matter for revegetation projects of mined spoils in the Brazilian FederalDistrict (DF). These sources were used for growing baru (Dipterix alata Vog.) on minedspoils in the Brazilian Cerrado and the growth and mortality of 99 seedlings treated with theseorganic matter soruces were measured. In 4 months, rates of survival ranged from 56.7%, fortrees treated with compost, to 96.7% for plants treated with sewage sludge. The compostseems to have toxic effects on seedlings, since the treatments with 35, 45 and 50 L/hollow hadno survivals. After the first period of growth, the study was able to show that the best rate forplant development with sewage sludge was 20 and 30 L/hollow (57% and 47). For plantstreated with compost, the best result was obtained with the smallest dosage (5L/hollow),where the growth is similar to the best results obtained with the sludge (47%). In larger dosesthe growth varied between 6% and 24%, span in which the results obtained in the controltreatments, chemical treatment (16%) and no treatment (12%) are also found. Therefore, theincrease in growth of the seedlings is a function of the dosage and type of organic materialemployed.